Democratic Practices in Indonesia's Multi-Party Election System During the Old Order Period - Suwito Suwito; Siti Ngainnur Rohmah (UIN JAKARTA, 2021)
People in the Old Order era were not fully familiar with the Democratic System. This is because during the old order the people were directly confronted with their participation in democracy through legislative elections. This study uses a qualitative research method with a normative juridical approach. The results of the study stated that for the first time in the Old Order period elections were held in 1955 to elect members of the legislature, while more than 25 political parties participated in the general election. In addition, the condition of the state during the old order was not yet stable politically, socially, and economically, due to pressure from outside and the new state gained independence.Keywords: Old Order; Democracy; Multiparty.